2020
DOI: 10.1097/spv.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Preoperative Medication Administration and Preoperative and Intraoperative Factors With Postoperative Urinary Retention After Urogynecologic Surgery

Abstract: Objectives The aim of this study was to determine if preoperative medication administration is associated with postoperative urinary retention (PUR) after urogynecologic procedures and identify preoperative and intraoperative factors that are predictive of PUR. Methods A retrospective review of patients who underwent prolapse and/or incontinence surgery was performed. The primary outcome was PUR, defined as postoperative retrograde void trial with postv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Thus, the published incidence of POUR broadly ranges between 15% and 45% 1–4,117–119 . Several studies have shown the rate of POUR after isolated MUS is less than when the MUS is placed at the time of prolapse repair, particularly those performed vaginally, with or without hysterectomy 20,120 . When it comes to colpocleisis, several studies have demonstrated that concurrent MUS does not increase the risk of POUR 31–35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the published incidence of POUR broadly ranges between 15% and 45% 1–4,117–119 . Several studies have shown the rate of POUR after isolated MUS is less than when the MUS is placed at the time of prolapse repair, particularly those performed vaginally, with or without hysterectomy 20,120 . When it comes to colpocleisis, several studies have demonstrated that concurrent MUS does not increase the risk of POUR 31–35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several commonly used perioperative medications affect voiding function. Anticholinergics, volatile anesthetics, opioids, and scopolamine may contribute to detrusor underactivity via their antagonistic action on muscarinic receptors 20,24–26 . Although the authors of these studies speculate that nonsteroidal anti-inflammatory drugs may be associated with detrusor underactivity due to inhibition of prostaglandin-mediated detrusor muscle contraction, these theories are based on observational studies from other surgical subspecialties 56,121 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously established benefits of ERAS in pelvic reconstructive surgery include decreased length of stay with similar rates of postoperative complications and emergency department visits, but with increased rates of PUR and 30-day readmission 15 . Schmidt et al 14 evaluated the association of PUR and ERAS preoperative medications, including phenazopyridine, acetaminophen, and gabapentin and found no increased risk of PUR. However, patients undergoing an isolated midurethral sling make up a minority of the study populations; therefore, the aforementioned findings may have been underpowered and not fully generalizable to this specific patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for urinary retention after pelvic reconstructive surgery include increasing age, medical comorbidities, degree of prolapse, procedure time, surgical blood loss, pain, and concomitant midurethral sling placement 10–13 . In addition, with the recent implementation of enhanced recovery after surgery (ERAS) protocols in pelvic reconstructive surgery, studies are forthcoming regarding the effects of these interventions on PUR 14 …”
mentioning
confidence: 99%